Cutting Edge: A Comparison of Contemporary Practices of Riparian Buffer Retention Around Small Streams in Canada, Finland, and Sweden. Issue 9 (16th September 2020) - Kuglerová, Lenka; Jyväsjärvi, Jussi; Ruffing, Claire; Muotka, Timo; Jonsson, Anna; Andersson, Elisabet; Richardson, John S.
Abstract: Forested riparian buffers are recommended to mitigate negative effects of forest harvesting on recipient freshwater ecosystems. Most of the current best practices of riparian buffer retention aim at larger streams. Riparian protection along small streams is thought to be lacking; however, it is not well documented. We surveyed 286 small streams flowing through recent clearcuts in three timber‐producing jurisdictions—British Columbia, Canada (BC), Finland, and Sweden. The three jurisdictions differed in riparian buffer implementation. In BC, forested buffers are not required on the smallest streams, and 45% of the sites in BC had no buffer. The average (±SE) width of voluntarily retained buffers was 15.9 m (±2.1) on each side of the stream. An operation‐free zone is mandatory around the smallest streams in BC, and 90% of the sites fulfilled these criteria. Finland and Sweden had buffers allocated to most of the surveyed streams, with average buffer width of 15.3 m (±1.4) in Finland and 4 m (±0.4) in Sweden. Most of the streams in the two Nordic countries had additional forestry‐associated impairments such as machine tracks, or soil preparation within the riparian zone. Riparian buffer width somewhat increased with stream size and slope of the riparian area, however, not in all investigated regions. We concluded that the majority of the streams surveyed in this study are insufficiently protected. We suggest that a monitoring of forestry practices and revising present forestry guidelines is needed in order to increase the protection of our smallest water courses. Key Points: We conducted regional‐scale field surveys in Canada, Finland, and Sweden to evaluate conditions of riparian buffers along small streams Riparian buffers along 286 small streams in Canada, Finland, and Sweden were on average 8.9, 15.3, and 4 m wide, respectively A revision and re‐evaluation of present forestry guidelines and regulations are needed in order to better protect small, forest streams